2019
DOI: 10.1111/1759-7714.13221
|View full text |Cite
|
Sign up to set email alerts
|

Front‐line treatment of ceritinib improves efficacy over crizotinib for Asian patients with anaplastic lymphoma kinase fusion NSCLC: The role of systemic progression control

Abstract: BackgroundApproximately 3%–5% of lung adenocarcinoma is driven by anaplastic lymphoma kinase (ALK) fusion oncogene, whose activity can be suppressed by multiple ALK inhibitors. Crizotinib and ceritinib have demonstrated superior efficacy to platinum‐based chemotherapy as front‐line treatment for patients with ALK‐positive advanced non‐small cell lung cancer (NSCLC). However, the direct comparison between them in the front‐line setting remains lacking.MethodsA total of 48 patients with ALK‐positive, previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(63 reference statements)
1
3
0
Order By: Relevance
“…However, this factor has been clarified by a Cox regression analysis, not fully but to a certain amount, as it was not associated with the treatment efficacy of ceritinib and alectinib. Furthermore, an alternative approach as earlier described, the propensity-scorematched analysis [23], was used to moderate this bias between the alectinib and ceritinib groups and confirmed the finding.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…However, this factor has been clarified by a Cox regression analysis, not fully but to a certain amount, as it was not associated with the treatment efficacy of ceritinib and alectinib. Furthermore, an alternative approach as earlier described, the propensity-scorematched analysis [23], was used to moderate this bias between the alectinib and ceritinib groups and confirmed the finding.…”
Section: Discussionsupporting
confidence: 61%
“…The treatment response, including complete response (CR), partial response (PR), stable disease, and progressive disease, was evaluated according to the Response Evaluation Criteria in Solid Tumors (version 1.1). The pattern of post-alectinib or post-ceritinib disease progression were also reviewed and defined as either systemic progression without prior CNS progression/death or CNS progression without prior systemic progression/death as earlier described [ 23 ]. The recording of toxicity profiles for alectinib or ceritinib treatment was performed by systemic chart review and toxicity was graded according to the National Cancer Institute Common Toxicity Criteria, version 5.0.…”
Section: Methodsmentioning
confidence: 99%
“…Although the efficacy of ceritinib versus crizotinib has not been evaluated in a direct head-to-head trial, a recently conducted retrospective analysis revealed a significantly longer median PFS with ceritinib versus crizotinib (32.3 months versus 12.9 months, log-rank p = 0.020) in treatment-naive Asian patients with advanced ALK -rearranged NSCLC. 19 The ORR observed with ceritinib in this Asian subgroup analysis (65.8% [95% CI: 54.0–76.3]) was numerically lower than that reported for crizotinib in Asian patients in the ALESIA (77%, N = 62), ALEX (76.8% [95% CI: 65.1–86.1], N = 69), PROFILE 1014 (70% [95% CI: 59.0–80.0], N = 77), and PROFILE 1029 (87.5% [95% CI: 79.6–93.2], N = 104) studies, and that reported for alectinib in Asian patients in the ALESIA (91%, N = 125) and ALEX (81.2% [95% CI: 69.9–89.6], N = 69) studies. 20 , 21 , 22 , 23 With all the limitations of indirect, cross-trial comparisons, the CNS response rate observed with ceritinib in this Asian subgroup analysis (11 of 25 patients [44%]; 95% CI: 24.4–65.1) was numerically higher than that reported for crizotinib (CNS responders: five of 23 patients [22%]; 95% CI: 8–44) but numerically lower than that reported for alectinib (CNS responders: 32 of 44 patients [73%]; 95% CI: 57–85) in Asian patients with similar conditions treated in the ALESIA study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, rebiopsy to discover the resistant mutations might be considered to determine the optimal treatment for ALK-inhibitor-resistant NSCLC [79]. In retrospective studies of ALK-positive advanced NSCLC, ceritinib demonstrated a longer median PFS compared to crizotinib for first-line treatment [80], and a second-generation ALK inhibitor, alectinib demonstrated a lower incidence of CNS progression and a tendency toward superior PFS compared to ceretinib in specific patients who had progressed on crizotinib [81].…”
Section: Alkmentioning
confidence: 99%